PENURUNAN TINGKAT PARTISIPASI POLITIK MASYARAKAT PADA PEMILIHAN WALIKOTA DUMAI TAHUN 2020 - Nurdina Fitri Arizal; Hasanuddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
One of the activities to channel public participation in a democratic country is by channeling votes during general elections held by the General Elections Commission. However, in the Dumai Mayoral Election which was held on December 9, 2020, the level of community participation during the election decreased compared to the 2015 Dumai Mayoral Election. Of course, this decline occurred not without cause, this could be influenced by several factors. This study aims to describe a decrease in the level of political participation in the 2020 Dumai Mayoral Election. In achieving the objectives of this study, the authors used the theory from Eep Saefulloh Fathah concerning four factors that cause a person not to exercise his right to vote. The research method used is a qualitative method by explaining descriptively. The type of research data used is primary data in the form of data obtained from research informants and secondary data obtained from related documents that can support data for research. The research location is in Dumai City, Riau Province. This study found that the decline in the level of community political participation in the 2020 Dumai Mayoral Election occurred due to technical factors in the holding of elections which could not be held properly due to the Covid-19 pandemic, meanwhile the socialization factor had been carried out to the maximum extent possible by the General Election Commission of Dumai City in accordance with the procedures for holding elections that have been determined. However, the political factor in this case, the death of one of the candidates for Mayor of Dumai made sympathizers lose interest in voting for him. Meanwhile, administrative factors have been held and produce voter data for the 2020 Dumai Mayoral Election. So the authors draw the conclusion that the 2020 Dumai Mayoral Election has been carried out in accordance with the stages and regulations set by the KPU. However, the decline in community participation that occurred was due to the main obstacle that occurred in the Covid-19 pandemic. So that it has an impact on reducing voter turnout, in accordance with the four factors that cause a person not to exercise their right to vote, namely technical factors, political factors, socialization factors, and administrative factors. Keywords: Decrease, Political Participation, Participation Level